2020
DOI: 10.4103/jfmpc.jfmpc_290_20
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice towards early screening of colorectal cancer in Riyadh

Abstract: Background and Aims: Colorectal cancer (CRC) is a common cause of mortality worldwide. It is preventable, treatable when detected early. The aim of this study is to assess knowledge, attitude and practice (KAP) of the participants toward CRC and its early screening, and identify the sources of information on the subjects. Methods: We conducted a cross-sectional study on the people 40y old and above at the primary care clinics at King Saud university medical city (KSUMC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 52 publications
11
37
0
Order By: Relevance
“…The study recognized that this method stressed on the importance of co-design input to give an intervention as CRISP sustainable with other risk methods. In Saudi Arabia , Alshammari et al,2020 concluded that the participant's knowledge and early screenings of Colorectal cancer are inadequate. They would undergo early screening if their doctors advised them to do that.…”
Section: Discussionmentioning
confidence: 99%
“…The study recognized that this method stressed on the importance of co-design input to give an intervention as CRISP sustainable with other risk methods. In Saudi Arabia , Alshammari et al,2020 concluded that the participant's knowledge and early screenings of Colorectal cancer are inadequate. They would undergo early screening if their doctors advised them to do that.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, as suggested by many authors, we also recommend that policymakers need to have a proactive attitude in implementing a unified national program for not only educating the population but also carry out preventive screening, medicine seminars, workshops, and awareness campaigns for the public about cancers in general and CRC in specific. [ 13 14 15 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…The women, as reported in 2010 [27]. Colorectal cancer is ranked first in men and the third rate of colorectal cancer was 9.6/100000 individuals in the Saudi population in 2015 [28].…”
Section: Attitude Of Participants About Early Detection Of the Invest...mentioning
confidence: 96%
“…In a Saudi study investigated the knowledge about colorectal cancer, it was found that 47% of participants heard about cancer screening, whereas 82.9% had a positive attitude to perform it if the doctor advised them [28].…”
Section: Attitude Of Participants About Early Detection Of the Invest...mentioning
confidence: 99%